Vai trò của kế toán quản trị trong quá trình ra quyết định chiến lược: Nghiên cứu định tính các trường hợp doanh nghiệp Việt Nam - Từ Thanh, Hoài; Trần Anh, Hoa; Nguyễn Phong, Nguyên (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The management accounting system is critical to the management activities and organizational performance of Vietnam firms, necessitating the promotion of effective management accounting practices in these businesses. This study used in-depth interviews with 15 managers in Vietnamese firms to develop a model for explaining the role of management accounting information and accounting capacity in promoting accountants' efforts to participate in strategic decision-making that improves business results. The study proposed a conceptual framework based on qualitative data analysis that reflects the mediating role of management accounting information in the effect of accountants' strategic decision-making on organizational performance, as well as the moderating role of accounting capacity in this effect. Along with contributions to the theoretical foundations of strategic management accounting, the research findings provide managerial implications for Vietnamese firms to effectively promote management accounting tools to enhance competitiveness in an age of globalization.
Keywords: Management accounting; Organizational performance; Accounting capacity; Strategic decision-making